Factor Influencing Sales Force Motivation: A Study of Pharmaceutical Industry in Aden, Yemen - Abdullah, Hanan Ali (2012)
One of the biggest challenge that business world is facing today is how to motivate employees to dedicate persistent and intensified efforts to achieve the organizational goals (Watson, 1994). Accordingly, employees’ attitude surveys have been used frequently to ascertain what sparks and sustains their desire to work harder. However, the motivation of the employees remained a complex puzzle since long (Wiley, 1997). It is generally accepted that motivated and committed sales force is one of the critical factors in the growth and profitability of the organizations. Yemen's pharmaceutical sales organizations to such enterprises as, developing fast and profits high, it really needs to motivate employee. The purpose of this study, focus on a Second-tier city in Yemen as the representative to determine the factors that influence pharmaceutical sales force motivation, used a sample of 199 participants among 23 pharmaceutical sales organizations in Aden. The study predicted three independent variables (payment, job security, and opportunities for advancement and development) though empirically investigated the relationship with motivation, and examined whether them effectively motivate pharmaceutical sales force. The finding showed that pay is not longer to severs motivate, based on Maslow’s needs hierarchy theory, job security as the security needs and opportunities need for advancement and development still more motivating them, especially, the needs for advancement and development is highlights significant motivator. It suggests that the intermediate needs and higher level of needs are important to motivate sales force that should be considered. Consequently, the study results will help practitioners in creating an effective incentive system to fostering sales force motivation leading to higher productivity and overall performance